A presença das TIC no curso de licenciatura em matemática da UNESP - campus Guaratinguetá - Haka, Caue Prata Pimentel [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This research shows an investigation on teaching formation in regards to the TICs. Our interest in this subject is due to the fact that new generations of students who attend school require that the classes make use of technology in the classroom environment. By following the phenomenological orientation we have carried out a study which involved a field research at the College of Engineering in Guaratinguetá using the graduate as well as senior students of the Bachelor's Degree in Mathematics of this university. We have analyzed the data under the light of texts of the following authors: Filho (2007), Valente (1993), Miskulin (2006), Borba and Penteado (2001) among others in order to understand the teacher`s formation process to act using technologies in the classroom and its relevance. The data that has been analyzed was obtained in interviews which were conducted with the students of this university. The interviews were transcribed and analyzed according to the rigor of phenomenological research procedures involving ideographic and nomothetic analysis. This analysis has led us to three open categories: 1) Mathematics learning through TICs; 2) Technologies that have been used; 3) Teacher`s role. By understanding the open categories we have been able to grasp that the students -future teachers- admit feeling capable of using technology in their classes, however their testimonies in regards to the TIC`s have led us to believe that there would be a reproduction of the content studied at their time at college without using further reflection upon the subject or autonomy in order to create new projects for teaching Mathmatics using these TICs

Esta pesquisa apresenta uma investigação acerca da formação docente com as TIC. Nosso interesse no tema se deve ao fato de reconhecer que as novas gerações de alunos que ingressam na escola cada vez mais necessitam que a educação não ignore a inserção das tecnologias na sala de aula. Seguindo a orientação fenomenológica realizamos o trabalho que envolveu uma pesquisa de campo na própria Faculdade de Engenharia de Guaratinguetá, tomando como sujeitos alunos do primeiro ao quarto ano do curso de Licenciatura em Matemática. Procuramos, com base em textos de Filho (2007), Valente (1993), Miskulin (2006), Borba e Penteado (2001) entre outros, compreender a formação de professores para atuar com as tecnologias e sua relevância. Os dados de análise foram obtidos em entrevistas realizadas com os sujeitos da pesquisa. As entrevistas foram transcritas e analisadas segundo o rigor da pesquisa fenomenológica envolvendo os procedimentos da análise ideográfica e nomotética. A análise nos levou a três categorias abertas: nomeadas Aprendizagem Matemática com o uso das TIC, Tecnologias Utilizadas e O Papel do Professor. Na interpretação das categorias abertas entendemos que os alunos, futuros professores, revelam que se sentem capacitados para utilização de tecnologias em suas aulas. Porém seus depoimentos acerca do uso das TIC nos leva a interpretar que haveria uma reprodução do que é visto na faculdade durante a sua formação sem que eles demonstrem um senso crítico ou autonomia para a idealização de novos projetos para o ensino de matemática com as TIC
Keywords: Tecnologia da informação; Fenomenologia; Professores - Formação; Teachers, Training of